2021
DOI: 10.4067/s0718-07642021000400077
|View full text |Cite
|
Sign up to set email alerts
|

Nivel de conciencia de la actividad y creación de información en medios digitales. Un estudio de caso en estudiantes universitarios chilenos

Abstract: Los objetivos de esta investigación fueron establecer el grado de conciencia de la actividad en la red en un grupo de estudiantes universitarios y, además, determinar cómo dicho grado condiciona la creación de información. En este estudio descriptivo no experimental de corte transversal, basado en el paradigma cuantitativo, se encuestó a 509 estudiantes a quienes se les aplicó dos cuestionarios, uno para establecer el nivel de conciencia de la actividad en red, y otro para describir los hábitos de trabajo y ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
1
0
0
1
Order By: Relevance
“…It is also observed that they make moderate use of online tools for collaborative content creation. As has been shown in other studies (Hernández-Orellana et al, 2021), low awareness of the activities to be developed is related to lower production of content and specific use of ICT for creation. In this sense, the development of PLE in general, and the creation of content in particular, becomes relevant, making the planning and incorporation of ICT in the curriculum a viable and successful strategy (Venegas-Álvarez & Proaño-Rodríguez, 2021), provided that it goes beyond the merely instrumental (Jato-Seijas et al, 2015) and focuses on innovative methodologies.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…It is also observed that they make moderate use of online tools for collaborative content creation. As has been shown in other studies (Hernández-Orellana et al, 2021), low awareness of the activities to be developed is related to lower production of content and specific use of ICT for creation. In this sense, the development of PLE in general, and the creation of content in particular, becomes relevant, making the planning and incorporation of ICT in the curriculum a viable and successful strategy (Venegas-Álvarez & Proaño-Rodríguez, 2021), provided that it goes beyond the merely instrumental (Jato-Seijas et al, 2015) and focuses on innovative methodologies.…”
Section: Discussionsupporting
confidence: 53%
“…También se observa que hacen un uso moderado de las herramientas en línea para la creación colaborativa de contenidos. Como se muestra en otros estudios (Hernández-Orellana et al, 2021), el bajo nivel de conocimiento sobre las actividades a desarrollar se relaciona con un nivel bajo de producción de contenidos y de uso específico de las TIC para la creación. En este sentido, el desarrollo de los PLE en general, y la creación de contenidos en particular, cobra relevancia, haciendo de la planificación y la incorporación de las TIC en el currículum una estrategia viable y exitosa (Venegas-Álvarez & Proaño-Rodríguez, 2021), siempre que no sea meramente instrumental (Jato-Seijas et al, 2015) y se centre en metodologías innovadoras.…”
Section: Marco Empíricounclassified